AKIBAT HUKUM JUAL BELI TANAH YANG STATUS TANAHNYA BELUM SELESAI - fauzia, anitha (NOVUM : JURNAL HUKUM)
The sale and purchase of land that has been plotted for housing development must be carried out through 3 (three) stages procedures, namely the first stage of the starting point, namely the aspect of land licensing (location), the second stage of the decision point, namely the aspect of land tenure (transfer of rights) and the third stage of the product point. namely the aspect of land certificates (rights to use buildings). In fact, the procedure was not carried out and resulted in the loss of the buyers of the 49 land plots. Taking into account the description, the problems discussed are the legal consequences of buying and selling land that has been plotted which has not completed the status of the land rights and whether the buyer of the land that has been plotted gets legal protection when the seller does not fulfill his obligations in the sale and purchase agreement. The sale and purchase of plots of land whose sales in installments can only be made with PPJB is based on the provisions of Article 1457 of the Civil Code, so that it only binds the parties who make the sale and purchase agreement. Sale and purchase with PPJB there has been no transfer of land rights because the formal requirements for the validity of the agreement have not been fulfilled, which is evidenced by a deed of transfer of rights before PPAT as referred to in Article 37 paragraph (1) PP No. 24 of 1997.